(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Problem-based learning (PBL) provides a number of potential language learning benefits through opportunities for authentic meaningful language use. Previous researches have also showed how PBL can generate students ’ idea and develop their writing skill independently. The aim of this study was to provide more conclusive results in the area of the relationship between extroversion and introversion and language performance in English as a Foreign Language (EFL) environment. The data was taken from pretest and posttest. There were 40 participants from one class of the fourth semester students of English Department who attended Genre Based Writing class taken by using purposive sampling. The research was conducted at English department of University of Sultan Ageng Tirtayasa, Banten. The main outcome of this research was to trigger students’ idea in order they could express their thought in the written form. Result indicated that through PBL, both introvert and extrovert students had better result in writing descriptive. Hence, it can be concluded that applying PBL as the method is necessary to trigger students’ idea for having writing product. It is because writing skill requires self-knowledge to express the thought process. Thus, students can experience the combination between process and product.